Analisis Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Citra Merek Terhadap Kepuasan Pelanggan Dan Dampaknya Pada Loyalitas Pelanggan Waroeng Spesial Sambal - Parman, Parman; Susanto, Susanto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
Companies in the future will increasingly depend on the brand, which means it is not enough to just-oriented services and products. To continue to improve its business and face competition Waroeng "SS" needs to improve as well as maintaining its customers with customer satisfaction, so that will have an impact on loyalty. This research aims to analyze the influence of the quality of service to satisfied customers, analyzing the influence of the quality of products against customer satisfaction, analyze the effect of brand image towards customer satisfaction, and analyze the influence of customer satisfaction on customer loyalty towards Waroeng "SS".The sampling techniques used in this research through purposive sampling and questionnaire created by using Likert scale. The analysis used i.e. structural equation modelling (SEM). The population in this research is the customers Waroeng "SS", with as many as 200 respondents number of respondents.Based on the results of the first hypothesis, hypothesis test indicates that the quality of service has no effect significant positive towards customer satisfaction. The second hypothesis test results indicate that the quality of the product has no effect significant positive towards customer satisfaction. The third hypothesis test results show that the positive effect of significant brand image towards customer satisfaction. The fourth hypothesis test results show that the positive effect of customer satisfaction significantly to customer loyalty.